Brome Hay Cost-Return Budget in Central and Eastern Kansas - Fausett, Marvin R.; Warmann, Gerald W. (My University, 1998)
This publication describes the yield levels, variable and fixed cost, and profit and return factors of producing brome hay in central and eastern Kansas.
MF2143_1998_10
Keywords: MF2143; Crops; Economics; MF